Education beyond school motivation program for STPM students, Sekolah Menengah Kebangsaan Hulu Kelang, Km 7, Jalan Hulu Kelang, 68000 Ampang, Selangor Darul Ehsan - Abdul Razak, Mohd. Abbas (2016)
This motivation program was organized for students who will be sitting for their STPM Examination this year (2016)